Comparison of Knee Range of Motion and Spatio-Temporal Parameters of Gait in Elite Men Athletes after Anterior Cruciate Ligament Reconstruction Using Two Surgery Methods - Fatemeh Alirezaei-Noghondar; Hossein Nabavinik; Maryam Amini (Vesnu Publications, 2019)
Introduction: The anterior cruciate ligament (ACL) is one of the supporting structures of the knee joint. ACL injuries are very common, and rapid postoperative return to exercise is the most important goal for athletes. Considering the different available surgical approaches, the purpose of the present study was to compare the knee range of motion (ROM) and spatio-temporal parameters during gait after ACL reconstruction using two different surgical methods in elite men athletes. Materials and Methods: In this quasi-experimental study, 25 elite athletes participated, ten subjects in the healthy group, eight in the allograft group, and seven in the autograft group. They were asked to walk along a walkway at preferred speed. Qualisys motion analysis system (eight camera) at a sampling frequency of 100 Hz was used to measure gait kinematic. Spatio-temporal and ROM parameters were extracted in three groups. One-way analysis of variance was performed to compare these variables at a significance level of P < 0.05. Results: There was no significant difference between the groups in terms of spatio-temporal parameters of step length, step time, stride length, stride time, cadence, velocity, stance phase, and swing phase of gait (P > 0.05 for all); however, the allograft group had lower mean values in all variables except for the cadence. In terms of knee ROM, with the exception of the minimum swing flexion that was significantly less in control group (P = 0.01), there was no significant difference between groups (P > 0.05). Conclusion: It seems that there is no functional difference between the two reconstruction types; therefore, it is not possible to make decision about knee reconstruction with regard tospatio-temporal parameters and kinematic pattern. We suggest that knee reconstruction be assessed from different viewpoints such as coordination pattern and muscle coordination.